The effect of H7 acupressure on amniocentesis anxiety in pregnant women: A randomized controlled trial - Mahyar Mohammadifard; Mahla Salarfard; Marzieh Samieean (Kashan University of Medical Sciences, 2021)
Background: Amniocentesis is the most common invasive procedure for diagnosing fetal abnormalities. Most pregnant women are anxious about fetal abnormalities and screening tests. Objectives: This study was conducted to determine the effect of H7 acupressure on amniocentesis anxiety in pregnant women. Methods: This clinical trial was conducted on 56 pregnant women candidates for amniocentesis. In the intervention group, acupressure was performed at H7 acupoint for 5 min in each hand, 30 min before amniocentesis, and then daily for 10 days. The control group did not receive any intervention. Data collection was done using a demographic questionnaire, the Spielberger state-trait anxiety inventory, and a daily acupressure recording checklist. Data were analyzed using the independent samples t-test, Chi-square test, repeated measures analysis, Bonferroni post hoc test, and paired t-test. Results: The mean state anxiety scores in the intervention group were 38.70 ± 5.64 and 30.22 ± 6.70 immediately and 10 days after amniocentesis. However, at the same times, the mean state anxiety scores in the control groups were 49.03 ± 2.30 and 50.86 ± 2.01, respectively, which were significantly higher than the intervention group (P < 0.001). The mean scores of trait anxiety were significantly lower in the participants of the acupressure group than the control group 10 days after amniocentesis (P < 0.001). Conclusion: The H7 acupressure could be effective in reducing state and trait anxiety in pregnant women during amniocentesis and when they are waiting for the test results.